Association Between Coronary Artery Ectasia and Neutrophil–Lymphocyte Ratio. (November 2013) - Balta, Sevket; Demirkol, Sait; Celik, Turgay; Kucuk, Ugur; Unlu, Murat; Arslan, Zekeriya; Balta, Ilknur; Iyisoy, Atila; Kocak, Necmettin; Haqmal, Hamidullah; Yokusoglu, Mehmet
Atherosclerosis plays an important role in the etiopathogenesis of coronary artery ectasia (CAE). Inflammation markers may play a part in the pathogenesis of CAE. We aimed to assess the association between the CAE and the neutrophil–lymphocyte (N/L) ratio. Consecutive eligible patients (n = 181) were divided into 3 groups: patients with CAE, those with newly diagnosed coronary artery disease (CAD), and those with a normal coronary angiogram. The N/L ratio and mean platelet volume (MPV) were measured as part of the automated complete blood count. There were no statistically significant differences in N/L ratio and MPV between the CAE and the CAD groups. The N/L ratio and MPV were significantly higher in patients in both CAE and CAD groups compared to those in the control group ( P < .01). An increased N/L ratio may play a role not only in the pathogenesis of CAD but also in the pathophysiology of CAE.